43 kDa Glycoprotein (gp43) from Paracoccidioides brasiliensis Induced IL-17A and PGE2 Production by Human Polymorphonuclear Neutrophils: Involvement of TLR2 and TLR4 - Taiane Priscila Gardizani; Amanda Manoel Della Coletta; Graziela Gorete Romagnoli; Rosana Puccia; Ana Paula Moreira Serezani; Ângela Maria Victoriano de Campos Soares; Luciane Alarcão Dias-Melicio (Journal of Immunology Research)
The glycoprotein gp43 is the major antigenic/diagnostic component of Paracoccidioides brasiliensis, one of the etiologic agents of paracoccidioidomycosis (PCM). Gp43 has protective roles in mice, but due to adhesive properties, this glycoprotein has also been associated with immune evasion mechanisms. The present study evaluated gp43 interaction in vitro with Toll-like receptors 2 and 4 (TLR2 and TLR4) present in polymorphonuclear neutrophils (PMNs) from healthy human individuals and the consequent modulation of the immune response through the expression and release of cytokines and eicosanoids. PMNs were incubated in the absence or presence of monoclonal antibodies anti-TLR2 and anti-TLR4 (individually or in combination) before gp43 stimulation. Then, PMNs were analyzed for the expression of both surface receptors and the detection of intracytoplasmic IL-17A and IL-4 using flow cytometry, while the production of PGE2, LTB4, IL-6, IL-10, IL-12, IFN-γ, and TNF-α was evaluated in the supernatants by enzyme-linked immunosorbent assay (ELISA). Our results showed that gp43 increased TLR2 and TLR4 expression by PMNs and induced PGE2 and IL-17A via TLR4 and TLR2, respectively. Thus, our data suggest that gp43 from P. brasiliensis might modulate host susceptibility to the fungal infection by affecting PGE2 and IL-17A production.